The Indigenous political in the post-Soviet Sakha Republic - Nikolaeva, Sardana (2022)
This research analyzes the socioeconomic and political structures, social and cultural networks, and forms of Indigenous mobilizations in a region where Indigenous political representation in the traditional sense is heavily circumscribed. Indigenous groups throughout the Russian Arctic are immensely affected by the state’s prioritization of extractive activities. This privileging of business interests often de-politicizes Indigenous mobilization by delegitimizing claims-making, undermining Indigenous territorial rights, and increasing economic disempowerment. Yet, I consider the de-politicization process as not only an important strategy for exercising state power, reinforcing dominant ideologies, and restricting politics, but also as a force that inspires countering efforts that can shape alternative political opportunities, expressions, and mechanisms. The research inquiry reveals that even though local Indigenous groups distance themselves from the overt politicization of Indigeneity, they still produce alternative narratives and employ strategies adequate to certain de-politicized contexts. In this sense, the Indigenous activists reformulate the pre-existing cultural, economic, and political meanings, values, and practices, challenging and subverting the bureaucratic forms of domination and discipline. Thus, the dissertation project focuses on local unpredictable and at times contradictory narratives and articulations of Indigeneity at the intersection of regional, national, and global histories. This research engages with the growing literature on post-Soviet theorizations of Indigeneity and of Indigenous subjects, and with Indigenous activisms, contributing to ethnography focused on Indigenous communities of Sakha Republic and their ambivalent position within the post-Soviet Russian state. The analysis is built on intensive academic and grey literature synthesis, on the yearlong ethnographic fieldwork in Yakutsk (a capital city) and the Olenyek district of Sakha Republic, integrating anthropological and ...